Hemifusomes and interacting proteolipid nanodroplets mediate multi-vesicular body formation - Amirrasoul Tavakoli; Shiqiong Hu; Seham Ebrahim; Bechara Kachar (Nature Communications)
Abstract The pleiomorphic structure and dynamic behavior of cellular endomembrane systems have been extensively studied using classical electron microscopy. However, fixation and staining constraints limit the in situ visualization of transient interactions, such as membrane fusion, scission, and intraluminal vesicle formation, potentially overlooking intermediate structures like membrane hemifusion. Using in situ cryo-electron tomography in four mammalian cell lines, we identify heterotypic hemifused vesicles featuring an extended hemifusion diaphragm consistently associated with a 42-nanometer proteolipid nanodroplet (PND). We designate these vesicular organelle complexes as “hemifusomes.” Hemifusomes constitute up to 10% of vesicular organelles at the cell periphery but do not engage in canonical endocytic pathways. These structures exhibit diverse conformations and frequently contain intraluminal vesicles. Building on the continuum of related morphologies observed, we propose that hemifusomes serve as platforms for vesicular biogenesis, mediated by the PND. These findings provide direct in situ evidence of long-lived hemifused vesicle complexes and introduce an ESCRT-independent model for multivesicular body (MVB) formation.